Formación en imagenología en la Universidad de Costa Rica: Retos y desafíos del proceso de actualización del currículo - Solís-Barquero, Sergio M.; Masís Calvo, Carolina; Jiménez Alpízar, Ana Carolina (Universidad de Costa Rica, 2020)
This essay pretends to analyze the challenges of a modification in the university curriculum of the medical radiation imaging career at the University of Costa Rica. The higher university education of imaging at the University of Costa Rica has its beginning in a Technical Training Program, which was evolving towards professionalization. However, despite the professionalization of imaging, there are still challenges in training, due to the constant change in technology, that must accompany the profession education. Advances in the field of radiotherapy to fight cancer, magnetic resonance imaging for the early diagnosis of neurodegenerative diseases and artificial intelligence, challenge the update of the higher education formation. The process that has been carried out in the creation of a professional output profile is presented, from which a reflection is made on how to train professionals in imaging. The educational process must be innovative with a human reflection of the ethics and the research, and of all the elements that characterize the graduate professional, framed in the historical moment of the Costa Rican superior education system.